Formation of Managerial Culture of the Future Engineers of Railway Transport - Oleksandr Halus (Pedagogical Discourse, 2017)
The article analyzes theoretical-practical approaches to the formation of managerial culture of the future engineers of railway transport. The essence of the concepts «culture», «professional culture», «managerial culture», «managerial culture of the future railway engineers» has been clarified. The peculiarities, elements, indicators of evaluation of the level of management culture have been analyzed. The important place in the formation of managerial culture of the future engineers of railway transport belongs to extra-curricular activities. The emphasis is placed on the importance of creating by each student their own professional portfolio. The psychological service of the institution of higher education, performing research, diagnostic, organizational, advisory, educational, stimulating, adaptive and other functions, properly contributes to the formation of the managerial culture of the future engineers of railway transport. This process is facilitated by the introduction of the innovative mass, group and individual forms of extra-curricular activities.